2017
DOI: 10.5430/jct.v6n1p65
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Internet Experience and Attitude on Student Preference for Blended Learning

Abstract: The purpose of this study is to investigate student experience with the Internet, and their attitudes towards using it, in an attempt to determine the impact of these experiences and attitudes on their view of the implementation of blended learning. Data from 142 Saudi students at a leading university in Saudi Arabia were collected via an online questionnaire. The results reveal that students have both experience with and positive attitudes towards using the Internet. Demographic variables had no effect on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
4
18
0
Order By: Relevance
“…Students' learning energy emerges positively. These findings are consistent with other findings in the context of similar problems (Alzahrani1, Majed G & O'Toole, John M., 2017) despite their college locus (Ja'ashan, M. H., 2015), (Alseweed, M. A., 2013).…”
Section: B Discussionsupporting
confidence: 92%
“…Students' learning energy emerges positively. These findings are consistent with other findings in the context of similar problems (Alzahrani1, Majed G & O'Toole, John M., 2017) despite their college locus (Ja'ashan, M. H., 2015), (Alseweed, M. A., 2013).…”
Section: B Discussionsupporting
confidence: 92%
“…A study revealed by Alzahrani & O'Toole (2017) that investigated student experience with the internet and their attitudes towards using it also found that the students seemed to have The Internet is likely to become an increasingly important way for students to keep new information up-to-date as it emerges. This may well affect future curriculum design, and this study suggests that student preference for one learning approach over other needs to be taken into account by instructional designers.…”
Section: The Results Of Students' Perceptionmentioning
confidence: 99%
“…A good experience score might be influenced by students' adequate access to the internet (100%). A research by Alzahrani and O'Toole, (2017) shows that student experience in following blended learning is influenced by the behavior of internet usage. Respondents who have longer experience in using the internet for learning have a better experience in following blended learning compared to respondents who have a shorter experience in using the internet to study.…”
Section: Discussionmentioning
confidence: 99%